Relationship-Oriented Sustainability Marketing : Concepts, Challenges, and Opportunities - Grunwald, Guido; Kara, Ali; Spillan, John E. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
This book explores sustainability marketing through the lens of stakeholder relationship-related concepts, with a particular focus on stakeholders within global value chains, relationships with the public, and those affiliated with governmental entities. Addressing a perceived gap in the current literature, the chapters delineate contemporary challenges and propose potential solutions for each stakeholder group, prioritizing the strategic and cross-instrumental dimensions. Offering a comprehensive examination of relationship-oriented sustainability marketing in the contemporary landscape, this work will acquaint researchers with the challenges related to stakeholder engagement in sustainability marketing and advance scholarship on effectively managing stakeholder relationships. Guido Grunwald is Professor of Business Administration, Marketing and Market Research in the Faculty of Management, Culture, and Technology at Osnabrück University of Applied Sciences, Lingen, Germany. His research interests center on customer behavior, sustainability and relationship marketing, and, more specifically, stakeholders' reactions to CSR communication and related corporate crises. Ali Kara is Professor of Marketing at the Pennsylvania State University, York Campus, USA. His research focuses on prediction of consumer decision making and choices based on quantitative modeling, empirical investigations of segmentation in international markets, and sustainability. John E. Spillan is Professor of Management in the College of Business and Economics at The University of North Carolina at Pembroke, USA. His research interests center on crisis management, international marketing, entrepreneurship and international business with specific interest in Latin America and Eastern Europe.
Keywords: Marketing.; Industrial management -- Environmental aspects.; Communication in organizations.; elektronické knihy; electronic books